The Principles of Housing Typology in Renewal of Deteriorated Fabrics (Case study: Tehran-Iran) - Rezaee , Naimeh; Ehsanfar , Alireza; Rabiee , Zienab (2008)
In recent years, in order to provide housing for the low-income population, different policies have been adopted in Iran. Yet, no attempts have been made to formulate the adequate housing typology for this population, so far. In recent years, with the promotion of discussions concerning the renewal of deteriorated urban fabrics, the necessity of formulating adequate housing typology for this population has become apparent. This is because these types of renewals often entail the demolishing of existing timeworn houses and constructing of new ones. The present essay tries to find an effective way for the construction of adequate houses for the habitants of these fabrics through examining the key factors in formulation of housing typology in deteriorated fabrics, and also through studying of two example cases in Tehran.